THE EFFECTIVENESS OF EEL Dr. C MODEL (ENROLL, EXPERIENCE, LABEL, DEMONSTRATE, REVIEW, CELEBRATE) FOR MATHEMATICS LEARNING OUTCOMES AT SEVENTH GRADE STUDENTS OF SMP NEGERI 3 KASIHAN - Lili Riana; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
The learning model is still used for the submission of verbal / lectures make students who have the ability to listen to high would be effective, but the students who have poor listening skills will be difficult to understand the material presented. It is thought to make low yields mathematics learning. This study aims to determine whether there is a difference in learning outcomes of students learning math using TANDUR and expository models and assess the effectiveness of the model TANDUR and the model Expository towards learning outcomes in mathematics class VII SMP Negeri 3 Kasihanin the Academic Year 2015/2016. The population in this study there are five classes. Samples were taken two classes with the technique of random sampling of classes and class VII D was chosen as an experimental class and class VII B as the control class. The design of this research is the control-group posttest only design. Data collection techniques using documentation technique and test technique. Data collection instrument in the form of test results to learn. Test data collection instruments used validity, distinguishing features and reliability testing. Data were analyzed using analysis prerequisite tests including normality test and homogeneity, continued to test the hypothesis using the T-test. Results of research on the significant level of 5% and dk = 52 show that: (1) There are differences in students' mathematics learning outcomes using models TANDUR with mathematics learning outcomes of students who use the Expository models. This is indicated by the value of tcount = 2.4125 and ttable = 2.01025 so tcount>ttable, and (2) a model TANDUR more effective than Expository models on the results of students' mathematics learning. This is indicated by the value of tcount = 2.4125 and ttable= 1.67492 so tcount >ttable.